Should team coaches care about justice? Perceived justice mediates the relation between coaches` autonomy support and athletes` satisfaction and self-rated progression - De Backer, M.; Boen, F.; Van Puyenbroeck, S.; Reynders, B.; Van Meervelt, K.; Vande Broek, G. (International Journal of Sports Science & Coaching, 2021)
In contrast to the many studies in the business setting, few sport scientists have studied the predictors of athletes`perception of justice. The present research aimed to determine the role of the interpersonal style of coaches (autonomysupport) in enhancing perceived justice and its impact on satisfaction and performance. More precisely, two independentstudies examined whether perceived justice mediated the relation between autonomy support on the one hand andathletes` satisfaction and their self-rated progression on the other hand. In Study 1, female team dancers (N=145)completed questionnaires assessing autonomy support, justice, and satisfaction. In Study 2, male handball players (N=102)completed the same questionnaire extended with self-rated progression. Structural equation modeling revealed a positivelink between athletes` perceived autonomy support of the coach and perceived justice. Subsequently, procedural-interactional justice predicted higher levels of satisfaction and self-rated progression, while a significant indirect effectwas found from autonomy support to satisfaction. Measurement and path invariance tests showed that the measurementscales and structural models were invariant across both samples. These findings signify the importance of autonomysupport and perceived justice to optimize team athletes` satisfaction and consequently their progression.